Research on Approaches for Regulation of the “Off-label” use of Medicinal Products in the European Union - Drenska M. (Sciendo, 2017)
Despite the increasingly strict legislation on medicinal products, the „off-label use“ or „use of medicinal product outside the approved summary of product characteristics (SmPC)“ is a weak point of today’s drug regulation and raises many questions about the risk, ethics, and legality of this type of practice. In recent years, through guidance and legal changes in some countries were defined the conditions and responsibilities, but in the most European countries still lack rules for off-label prescribing. The purpose of this study was to identify and analyse different approaches to regulation, adopted by some member states as well as to summarize the efforts in demand of common harmonized approach to solve this problem within the European Union. In the study, we used the available regulatory information in different electronic resources associated with the off-label drug use in selected European countries without limited time range. The results show that decisions taken to regulate the issue have significant differences and specific approach, while none of them is enough satisfactory and comprehensive. In conclusion, it can be claimed that the existing regulatory rules in various countries require significant improvement and update.